2010
DOI: 10.2147/ijn.s11727
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of silver nanoparticles in Dalton’s lymphoma ascites tumor model

Abstract: Nanomedicine concerns the use of precision-engineered nanomaterials to develop novel therapeutic and diagnostic modalities for human use. The present study demonstrates the efficacy of biologically synthesized silver nanoparticles (AgNPs) as an antitumor agent using Dalton's lymphoma ascites (DLA) cell lines in vitro and in vivo. The AgNPs showed dose-dependent cytotoxicity against DLA cells through activation of the caspase 3 enzyme, leading to induction of apoptosis which was further confirmed through result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(71 citation statements)
references
References 35 publications
1
68
0
2
Order By: Relevance
“…Color formation rapidly occurred in this mixture, possibly because of the reaction between Ag ions and NAR [12,28]. The synthesis of AgNPs was confirmed using UV–visible spectroscopy (UV–vis).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Color formation rapidly occurred in this mixture, possibly because of the reaction between Ag ions and NAR [12,28]. The synthesis of AgNPs was confirmed using UV–visible spectroscopy (UV–vis).…”
Section: Resultsmentioning
confidence: 99%
“…Gurunathan et al demonstrated the anti-angiogenic properties of AgNPs in vascular endothelial cells, which showed equivalent potency to a natural anti-angiogenic molecule, known as pigment epithelium-derived factor, by inhibiting the phosphorylation of protein kinase B/Akt [11]. SriRam et al demonstrated the potential cytotoxicity against Dalton’s lymphoma ascites (DLA) and DLA-induced tumors in mice, with significantly increased survival times in the tumor mouse model compared to the untreated group [12]. Low concentrations of poly ( N -vinyl-2-pyrrolidone)-coated AgNPs inhibited the viability of acute myeloid leukemia cells and the viability of K562 cells in a dose-dependent manner after entering the cells via endocytic pathway endosomes [13].…”
Section: Introductionmentioning
confidence: 99%
“…The IC 50 value of biosynthesized AgNPs against HeLa cells at 200  μ g/mL concentrations (Figure 6(a)). Previously, synthesized AgNPs inducing cytotoxicity were discussed by Sriram et al [42] and Safaepour et al [43]. …”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35][36][37][38] Ag NPs are also potent sensitizers for cancer chemotherapy 39 and radiotherapy, 40,41 and show significant antitumor activity in several animal models. [42][43][44] However, whether Ag NPs can induce autophagy and how this might affect the anticancer activity of Ag NPs have not been reported. In this report, we showed for the first time that Ag NPs effectively induced cytoprotective autophagy, and that inhibition of autophagy significantly promoted the antitumor activity of Ag NPs, as illustrated in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%